The Urgency of Interpersonal Skills, Leadership and Self-Discipline for Vocational High School Students Majoring in Aesthetics and Hairdressing - Widarto Widarto; Septiari Nawanksari; Putri Marganing Utami (Universitas Pendidikan Ganesha, 2024)
Soft skills, especially interpersonal skills, leadership and self-discipline, are very important to support 21st century skills for Vocational High School (SMK) students. The purpose of this research is to analyze the extent of the influence of interpersonal skills, leadership, and self-discipline on the critical thinking abilities of grade 11 VHS students in the Department of Aesthetics and Hairdressing (A&H). This research is correlational research conducted using a quantitative approach. A total of 141 A&H Department students from five vocational high schools in DIY were selected as research samples. The sampling technique used was stratified random sampling. The research instrument consists of a questionnaire with a 4 point Likert scale. Data were analyzed using regression analysis and SEM analysis. The research results show that interpersonal skills, leadership and self-discipline have a significant effect on the critical thinking abilities of A&H Department students. The results showed that interpersonal skills, such as the ability to communicate and work in a team, are very important for students because jobs in the aesthetics and hairdressing fields often involve direct interaction with clients. Leadership skills are also needed, especially when students have to lead projects or manage their own businesses. The implications of this research lie in the curriculum, the curriculum needs to be expanded to not only focus on technical skills, but also provide a significant portion of the development of soft skills, including effective communication, team management and leadership.